Pengaruh Sosialisasi, Pembaharuan Sistem Administrasi, dan Insentif Pajak terhadap Performa Institusi - Ilmawan, Patah Fatwa; Indarto, Indarto; Budiati, Yuli (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
This exploration focuses on the effectiveness of the East Semarang Pratama Tax Office (KPP Pratama) in achieving its targets through public education, administrative modernization, and the implementation of tax relaxation. This study positions taxpayer discipline as an intermediary element linking policy to institutional outcomes. By involving all office staff (97 respondents) as research subjects through a census approach, data collected through a questionnaire instrument was processed using the SEM-PLS technique. The research findings confirm that massive outreach, a reliable bureaucratic system, and the tax amnesty program have a strong linear correlation with public compliance behavior. This positive impact simultaneously has implications for strengthening productivity and achieving overall organizational targets.